2020
DOI: 10.1039/d0qi00442a
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic oxidation catalyzed by polyoxometalates associated to an artificial reductase at room temperature and in water

Abstract: Four polyoxometalates (POMs) were combined with an artificial reductase based on polyethyleneimine (PEI) and flavin mononucleotide (FMN) which is capable of delivering single electrons upon addition of nicotinamide adenine dinucleotide (NADH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…It was more recently shown that this artificial reductase was also able to reduce efficiently polyoxometalates in water which allowed them to catalyze the sulfoxidation of thioanisole derivatives by O2. [32] Finally we demonstrated that the reduced, artificial flavoenzyme could also directly activate molecular dioxygen under aerobic conditions and catalyzed at room temperature in water the Baeyer-Villiger reaction. [33] This afforded a new environmentally friendly oxidation process for the direct incorporation of an oxygen atom into small organic molecules.…”
Section: Reductive Activation Of O2 In the Presence Of Artificial Redmentioning
confidence: 89%
“…It was more recently shown that this artificial reductase was also able to reduce efficiently polyoxometalates in water which allowed them to catalyze the sulfoxidation of thioanisole derivatives by O2. [32] Finally we demonstrated that the reduced, artificial flavoenzyme could also directly activate molecular dioxygen under aerobic conditions and catalyzed at room temperature in water the Baeyer-Villiger reaction. [33] This afforded a new environmentally friendly oxidation process for the direct incorporation of an oxygen atom into small organic molecules.…”
Section: Reductive Activation Of O2 In the Presence Of Artificial Redmentioning
confidence: 89%
“…Crystallographic and computational studies performed by us, and also others, have shown that POMs interact preferentially with positive patches of the protein surface, imparting high regioselectivity to the hydrolytic cleavage obtained 31 33 , 37 , 50 , 52 , 61 . Thus, we hypothesized the POM ligands could also be used to direct the selectivity in other types of reactions, such as the radical ones observed in MCO reactions 62 65 . Developing metal-POMs oxidative reactivity towards proteins would also circumvent key limitations of conventional metal complexes, as MS-POMs are stable to a wider range of pH 66 , and the highly oxidized nature of the metals in their structure prevents competition with the protein substrate, increasing catalyst versatility, and life-span 66 .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] The Keggin type is the most widely studied type of POMs. [21][22][23][24] Due to its excellent structural stability and easy modication, Keggin-type POMs can play different roles in the design and synthesis of peculiar structural compounds. Compared with other POMs, [BW 12 -O 40 ] 5À ({BW 12 }) has a high surface charge density and is more likely to have a mutual effect with transition metals, which is conducive to the formation of more complexes.…”
Section: Introductionmentioning
confidence: 99%